KEWENANGAN OPERATOR TERMINAL DALAM PENGAWASAN DAN PENINDAKAN TERHADAP ANGKUTAN LIAR - Widodo, Ugen Cahyo; Borman, M.Syahrul; Hidayati, Nur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research is motivated by the prevalence of illegal transportation operating without official permits within and around public terminals, disrupting order and safety in land transportation. The research problems include: (1) the authority of terminal operators in supervising illegal transportation, and (2) the legal sanctions applicable to illegal transportation within and outside the terminal. This study employs a normative legal research method using statutory and conceptual approaches. The findings indicate that the authority of terminal operators is administrative in nature, limited to checking administrative completeness and operational arrangements, without repressive authority to impose criminal sanctions directly. The main obstacles identified include regulatory gaps, overlapping authorities among institutions, limited facilities and human resources, and weak inter-agency coordination. This research recommends strengthening the legal basis of terminal operators’ authority, enhancing inter-agency coordination, and reformulating integrated supervision policies to achieve orderly, safe, and law-based public transportation